Tracing Pancasila: Unveiling the impact of the Pancasila student profile strengthening project on student well-being in Indonesia - Solehuddin, M.; Budimansyah, Dasim; Dahliyana, Asep (Jurnal Cakrawala Pendidikan, 2024)
This research aims to investigate the impact of policies to strengthen the Pancasila Student Profile project on the welfare of students in Indonesia. This research seeks to understand how implementing this policy, especially through the Merdeka Curriculum and the Strengthening Pancasila Student Profile (P5) Project, affects student welfare. This research methodology used a quantitative approach. Data collection was carried out by surveying 2,755 students from 17 provinces in Indonesia. Quantitative data was analyzed using statistical techniques to evaluate the impact of policies on student welfare. The results of this research indicate that the implementation of the policy to strengthen the Pancasila Student Profile project has a positive impact on student welfare. Cognitive, psychological, and social dimensions of well-being showed significant improvements. In addition, variables such as students' hope, optimism, and cognitive engagement are also positively correlated with the implementation of the policy. This research has great significance in the context of educational development in Indonesia. The research findings can make an important contribution to the understanding of how educational policies, such as the Merdeka Curriculum and the Pancasila Student Profile Strengthening Project, can play a role in improving student welfare. The implications of this research can help policymakers, educators, and educational practitioners to design more effective interventions to improve students' quality of life in educational environments